The Wills Eye STRABISMUS SURGERY Handbook - Nelson, Leonard; Levin, Alex (CRC Press, 2015)
Although residents and pediatric ophthalmology fellows examine patients in the clinic, they may not be involved in surgery on the same patients and even less often get to follow the progress of these patients postoperatively. The Wills Eye Strabismus Surgery Handbook is designed to address this challenge in residency and fellowship education as a manual focused on developing surgical plans for strabismus patients. Drs. Leonard B. Nelson and Alex V. Levin and their contributors have organized The Wills Eye Strabismus Surgery Handbook to allow for the reader to take notes regarding their own diagnosis and treatment plan for each case that is presented. This workbook style and its practical, easy-to-read format make this resource useful for written and oral board preparation, and as a handy reference guide for use long after exams are over. Each chapter presents an introduction into the decision-making process for a specific strabismus condition, followed by the surgical plans selected by three expert Wills Eye Strabismus Center strabismologists with regard to their approach to the presented case. Summary remarks by the chapter editor briefly review the basic concepts in developing a diagnosis and treatment plan while bringing together the varied opinions offered by the strabismologists in order to put them in context. Topics covered include: Strabismus surgery decision making Esotropia Exotropia Dissociated vertical deviation Cranial nerve palsies Strabismus syndromes Strabismus in systemic disease Reoperations Nystagmus Other complex strabismus cases The Wills Eye Strabismus Surgery Handbook is an essential resource for residents and pediatric ophthalmology fellows, as well as other ophthalmologists, looking to develop their surgical planning skills. It is a helpful field guide for any ophthalmologists who does strabismus and who is looking for a handy addition to their reference shelf.